Ownership structure and market value of commercial banks in Nigeria: How significant is the retail owners, domestic institutions ownership, foreign institutions ownership, Government - Olakunle Abraham Olateju; Olateju, Dare John; Olagunju, Adebayo; Adebayo, Aderemi Olalere; Olowookere, Johnson Kolawole (Indonesian Management and Accounting Research, 2022)
This study investigates the relationship between ownership structure and the market value of commercial banks in Nigeria, utilizing agency theory as a theoretical framework. Panel data from 2014 to 2022, comprising 63 firm-year observations from 7 commercial banks, is analyzed using Fully Modified Least Squares (FMOLS) and Phillips-Perron cointegration tests. The findings reveal that domestic shareholdings have a statistically significant positive effect on bank valuations, while foreign and government shareholdings have significant negative effects. The results suggest that increased domestic investment enhances market value, whereas higher foreign and government ownership may reduce it. These findings underscore the importance of ownership structure in shaping market perceptions and provide valuable insights for policymakers aiming to optimize ownership arrangements in the Nigerian banking sector.